Methods of taxation under tax control in Algeria:‎ Reality and suggestions - Bessas, ahmed (Dirassat Journal Economic Issue, 2016)
It has proved that a fiscal control which is carried out by the tax administration is the most important means to fight the negative behavior of the tax payers. These negative behaviors have a bad impact and reduce dramatically tax bases. In order to fight against these behaviors, the tax administration uses the fiscal control and works on providing means and competencies in low and accounting which acquire high level of skills. Through these means, it could quickly and in the required deadlines unveil errors and manipulations that have been made by taxpayers. They apply in accordance with regulations, required procedures and penalties on taxpayers. These later affect the behavior of taxpayer so he will be more interested and committed in announcing his tax statement accurately and truthfully